A Study on the Implementation of E-Commerce in Malaysian Small and Medium Electrical and Electronics Industries - Adel, I. Bakkar (2004)
The importance of E-commerce cannot be ignored and Malaysia like other countries has also embarked on this new way of doing business. E-commerce is relatively new in Malaysia, and the government has initiated the Multimedia Super Corridor (MSC) in the process of bringing the country to the frontier of global E-commerce. Several agencies in Malaysia have been established to help implementing E-commerce. The strategic importance of small and medium enterprises (SMI) in economic development is widely recognized in both developed and developing countries. In Malaysia, there have been numerous supporting programmes provided by the government agencies and institutions aimed at fostering the development of (SMI).This study investigates the status and barriers for E-commerce implementation in Malaysian small and medium electrical and electronics industries (SMI). Five hundred companies (from SIMDEC Directory) located entirely in the Klang Valley region were chosen as respondents for this current study. Survey questionnaires were sent out to these companies to gather relevant information regarding their E-commerce background. The questionnaires were aimed towards decision-makers of the companies. Fifty-one companies (10.2 %) responded to the questionnaire.From the survey conducted, it was observed that 51 % of the companies studied have not implement E-commerce technology. The study revealed that the major reasons for not implementing E-commerce were: the lack of funding, the lack of knowledge on E-commerce, infrastructure, security issues, lack skillful human resources, and attitude towards E-commerce. These were the major reasons why SMIs did not implement Ecommerce.This study also highlights the main reasons for implementation E-commerce by some Malaysian small and medium electrical and electronics industries. This study identify the following factors for the implementation; enhance company’s image, expand to international market, build competitive advantage, gain competitiveness in marketplace, increase customer sophistication, and increase productivity. From the data gathered, it has been found that 52 percent of small and medium electrical and electronics industries aim to expand their businesses locally as well as globally. The results also suggest that the accessibility of support programmed for the development of E-commerce within the (SMI) is still limited despite the fact that a high policy agenda has been introduced to promote the development of (SMI) in Malaysia. The results of this study will serve as feedback to Malaysian authorities to step up their efforts in promoting Ecommerce awareness, and adopting new and enabling technologies in Malaysian (SMI) companies. It is also hoped that this study can provide a guideline for Malaysian companies in evaluating and formulating effective strategies and policies into E-commerce.